Assessment of the Competitiveness of the Tourist Enterprise in the Modern Conditions (Economics and region, 2020)
The theoretical and methodological basis of the study are scientific developments of domestic and foreign scientists related to competitiveness as a priority economic factor of sustainable development and functioning of the tourist enterprise in a changing environment, materials of specialized scientific conferences and symposia. The article considers and highlights the problems of competitiveness of the tourist enterprise as a separate subject of research. It is revealed that the recent strategic changes, which are the key to creating future competitive advantages, are the result of ensuring the long-term development of the tourist enterprise in the relevant competitive economic conditions.      It is shown that the most acute problem of assessing the level of competitiveness of a tourist enterprise is the lack of information about competitors, which leads to incomplete analysis, the use of subjective scores, high financial and time costs to conduct a study of competitiveness. The main competitive strategies of the enterprise which allow to win in struggle against competitors are analyzed. Emphasis is placed on the need to develop stages of systematic study of the competitiveness of tourism enterprises, which will allow to characterize the level of their competitiveness, even in conditions of information lack. The obtained results of the research are the basis for the scientific substantiation of the process of managing the competitiveness of tourist services (goods), which is one of the sub-goals of managing the competitiveness of the enterprise and should be subordinated to it. The results of the study are the basis for effective strategic management of tourism enterprises of Ukraine, capable of enhancing the competitiveness of the industry.
Keywords: enterprise competitiveness; tourist enterprise; tourist services; strategy; competitive advantages; information; markets